2016
DOI: 10.24200/sci.2016.2095
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Capacity of Square Footings on Sand Reinforced with Dissimilar Geogrid Layers

Abstract: This paper aims to investigate the likely e ects of geogrid reinforcement con guration on the bearing capacity of footings. Using geogrid reinforcement layers with certain total areas in various uniform and non-uniform arrangements, the bearing capacities of footing models on reinforced sand beds were determined and compared. The rst arrangement was the conventional uniform layout in which three geogrid layers of equal dimensions were considered. In the second group, the same amount of geogrids was used in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
2
1
0
4
Order By: Relevance
“…6 shows the effect of position of one geogrid reinforcement layer on the relation between the rut depth and the number of load cycles, test series II. The results concluded that the optimum position of one geogrid reinforcement layer is at the upper quarter of the base course layer and not at the interface as previously showed by Barksdale et al, (1989), Chan et al, (1989), Degroot (1986), McGown and Andrawes (1977) and Rowshanzamir and Karimian (2016).…”
Section: Resultssupporting
confidence: 70%
“…6 shows the effect of position of one geogrid reinforcement layer on the relation between the rut depth and the number of load cycles, test series II. The results concluded that the optimum position of one geogrid reinforcement layer is at the upper quarter of the base course layer and not at the interface as previously showed by Barksdale et al, (1989), Chan et al, (1989), Degroot (1986), McGown and Andrawes (1977) and Rowshanzamir and Karimian (2016).…”
Section: Resultssupporting
confidence: 70%
“…In comparison with similar research performed by [35], where the inverse trapezoidal layout was found to yield the greatest BCR values, attributed to the fact that putting lengthy layers of reinforcement at upper levels near the footing base may lead to higher bearing capacity improvement; and the least BCR values were found for trapezoidal layout, considered as an indication that placing small size layers in upper levels of sand bed may yield low reinforcement efficiency [35], we found that the trapezoidal arrangement, for both biaxial and multiaxial geogrids, leads to a higher BCR. were carried out under existing standards and procedures, and the test procedures were controlled, this variation could probably be explained by considering that a trapezoidal arrangement covers a larger fault surface, as can be seen in figure 19c, thus giving a greater increase in load capacity, which still needs to be studied in future research.…”
Section: Discussionsupporting
confidence: 70%
“…Nosivost tla se povećala i kod uporabe jednog sloja geomreža na spoju slojeva različitog tla uz armiranje i gornjega površinskog pjeskovitog sloja [17]. Rowshanzamir i Karimian [18] su u radu istraživali učinke geometrije polaganja slojeva geomreža kod armiranja tla. Proveli su pokuse s postavljanjem armaturnih slojeva geomreže u različitim formama kod armiranja pjeskovitog tla.…”
Section: Tablica 1 Prikaz Značajnijih Istraživanja Nosivosti Tla Armi...unclassified